Everything is Psycholinguistics: Material and Methodological Considerations in the Study of Compound Processing. (27th June 2016) - Libben, Gary
Abstract: Compound words allow us to investigate lexical storage, retrieval, and interpretation. The role of storage and computation in compound processing is reviewed. It is claimed that morphological processing is automatic and obligatory, and that multi-morphemic words require resolution of a conflict between whole-word and constituent activation. This leads to the conclusion that morphological constituents are created through morphological processing so that strawberry comes to be composed of straw- and -berry ; these constituents are positionally bound so that berry-, -berry, and berry are distinct processing units. This proliferation of morphological representations resolves long-standing puzzles concerning semantic transparency and challenges traditional psycholinguistic approaches that investigate the effect of some independent variable (such as semantic transparency) on task performance as a dependent variable. It is suggested that psycholinguistic inquiry may be understood as the study of the correlation of dependent variables within the language processing system.